Design of Bacterial Cultures in Fermented Functional Maize Product Formulation - Zuzana Matejčeková; Anna Mikulajová; Eva Vlková; Denisa Liptáková; Silvia Mošovská; Eva Hybenová; Ľubomír Valík (Polish Journal of Food and Nutrition Sciences)
In this work, the effect of single fermentation of maize mashes with Fresco DVS 1010 culture ( Lactococcus lactis ssp. lactis , Lactococcus lactis ssp. cremoris , and Streptococcus thermophilus ) was studied for 8 h (37°C) followed by a storage period of 21 days (6°C). Although milk is a typical growth medium for lactic acid cocci of the Fresco culture, fermentation increased its counts by about 3 log CFU/mL after 8 h (37°C), whereas pH of 4.54 and 4.69 was achieved after the fermentation in products with sucrose and caramel, respectively. Fermentation process was observed to significantly increase (p<0.05) the total phenolics content (143.9-206.1%) and the antioxidant activities (53.7-107.4%) of the samples. Potentially probiotic Lactobacillus plantarum HM1, Bifidobacterium choerinum K1/1, Bifidobacterium pseudolongum K4/4, Bifidobacterium animalis ssp. animalis J3II, and Bifidobacterium thermophilum DSM 20212 inoculated after the fermentation process were well maintained (>5 log CFU/mL) in combination with the mixed Fresco culture in the prepared maize products within 21 days of storage. Based on the overall sensory acceptance, caramel mashes after 12 days of storage period were evaluated as satisfactory (2.4 to 3.1 from 4.0), while 21-day stored products achieved good acceptability scores (3.0 to 3.6 from 4.0), hence the tendency of the positive effect of prolonged shelf-life was noted.